Solid state physics : advances in research and applications. - Spaepen, Frans (Solid-state physics ;, 1997)
Solid State Physics, Volume 50 continues the series' tradition of excellence by focusing on the optical and electronic properties and applications of semiconductors. All of the topics in this volume are at thecutting-edge of research in the semiconductor field and will be of great interest to the scientific community.